The legend of Ulenspiegel and Lamme Goedzak, and their adventures heroical, joyous and glorious in the land of Flanders and elsewhere (London : William Heinemann, 1922)
Bibliotheek Camille Huysmans
Engels
Meerdelige publicatie
Keywords: Tijl Uilenspiegel; legenden; folklore